2017
DOI: 10.1142/s0219691317500370
|View full text |Cite
|
Sign up to set email alerts
|

Multi-focus image fusion and super-resolution with convolutional neural network

Abstract: The aim of multi-focus image fusion is to create a synthetic all-in-focus image from several images each of which is obtained with different focus settings. However, if the resolution of source images is low, the fused images with traditional fusion method would be also in low-quality, which hinders further image analysis even the fused image is all-in-focus. This paper presents a novel joint multi-focus image fusion and super-resolution method via convolutional neural network (CNN). The first level network fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…It is concluded from the results shown in these tables that the proposed algorithm provides better objective results as compared to other algorithms. The statistical results obtained for different multifocus images has shown that the proposed algorithm in this paper shows better performance than compared to other methods published recently elsewhere [24,27,31,36,37,38].…”
Section: Modified Principal Component Analysis (Mpca)mentioning
confidence: 58%
“…It is concluded from the results shown in these tables that the proposed algorithm provides better objective results as compared to other algorithms. The statistical results obtained for different multifocus images has shown that the proposed algorithm in this paper shows better performance than compared to other methods published recently elsewhere [24,27,31,36,37,38].…”
Section: Modified Principal Component Analysis (Mpca)mentioning
confidence: 58%
“…It is concluded from the results shown in the table 1 to table 6 that the proposed FPDCT with modified PCA method provides better objectives than other state of the art PCA based algorithms. The statistical results obtained for different multifocus images has shown that the FPDCT algorithm shows superior performance as compared to other methods [24][25].…”
Section: Resultsmentioning
confidence: 96%
“…Recently Bin Yang et al [24] proposed both multi-focus image fusion and super-resolution algorithms via convolutional neural network (CNN). The main idea of this work is to learn the fusion weights using neural network technology to fuse the patches of multi-focus images.…”
Section: Introductionmentioning
confidence: 99%
“…Zhen et al [34] proposed an algorithm to improve accurate contrast enhancement, but it has a poor effect on over-exposed regions. Some HDR algorithms [35][36][37] based on deep learning have been proposed to generate HDR images, but these algorithms do not solve the problems of camera shaking and object movement.…”
Section: Related Workmentioning
confidence: 99%